2015
DOI: 10.3389/fpls.2015.00291
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine metabolism in flax in response to treatment with pathogenic and non–pathogenic Fusarium strains

Abstract: Flax crop yield is limited by various environmental stress factors, but the largest crop losses worldwide are caused by Fusarium infection. Polyamines are one of the many plant metabolites possibly involved in the plant response to infection. However, in flax plants the polyamine composition, genes involved in polyamine synthesis, and in particular their regulation, were previously unknown. The aim of this study was to investigate the polyamine synthesis pathway in flax and its involvement in response to patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 41 publications
1
24
0
4
Order By: Relevance
“…In addition, Put and Spd accumulated in apoplasts when healthy leaves of rice plants were inoculated with the hemibiotrophic fungus Magnaporthe grisea (race 031) (Yoda et al ., ). A recent article reported that the Put level, but not Spd or Spm, showed considerable increase during infection with two pathogenic strains and one non‐pathogenic strain of Fusarium in flax, whereas the transcript levels of PA degradation genes were not changed (Wojtasik et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, Put and Spd accumulated in apoplasts when healthy leaves of rice plants were inoculated with the hemibiotrophic fungus Magnaporthe grisea (race 031) (Yoda et al ., ). A recent article reported that the Put level, but not Spd or Spm, showed considerable increase during infection with two pathogenic strains and one non‐pathogenic strain of Fusarium in flax, whereas the transcript levels of PA degradation genes were not changed (Wojtasik et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Other studies have addressed responses of specific genes or gene families upon F. oxysporum attack based on the knowledge of the general responses in plant-pathogen interactions; such studies display different stages and mechanisms of defense. For example, a study of changes in polyamine gene expression and polyamine metabolites in response to F. oxysporum and F. culmorum (Wojtasik et al, 2015), was explored due to the regulation of arginine decarboxylase in the aforementioned cDNA subtraction study. Others have used transgenics to modulate secondary metabolites (carotenoid and flavonoid biosynthesis) to increase resistance of flax to the pathogen, using the antioxidant action of these compounds against the reactive oxygen species produced upon infection (Lorenc-Kukuła et al, 2007, 2009; Boba et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lowest induction in the gene expression levels and PA accumulation was detected in the case of the non-pathogenic Fusarium oxysporum strain. Differences observed between the two pathogenic strains also suggested, that the two pathogens have different mechanisms for plant tissues penetration, and they also induced different defence mechanism in lax seedlings [16].…”
Section: Plant-pathogen Interactionsmentioning
confidence: 94%